Clinical photoacoustic/ultrasound dual-modal imaging: Current status and future trends - Wen, Yanting; Guo, Dan; Zhang, Jing; Liu, Xiaotian; Liu, Ting; Li, Lu; Jiang, Shixie; Wu, Dan; Jiang, Huabei (Frontiers in Physiology, 2022)
for a natural integration of PAT and US imaging in a combined modality. Due to the similarities in PAT and US signal acquisition and processing, the combination of PAT and US imaging will create a new dual-modal imaging to achieve certain clinical applications. In recent years, particular attention is paid to those PAT/US dual-modal systems and highlighting the mutual benefit of using synchronously in clinical usage, which has the potential to substantially improve the specificity and sensitivity in diagnosing disease. In this review, the current PAT/US dual-modal imaging systems (i.e. acoustic transducers and hardware) are discussed in detail, and their promising clinical application are compared systematically. Finally, this review briefly discussed the potential impacts of these combined systems in the near future.